2019
DOI: 10.3390/ijerph16234712
|View full text |Cite
|
Sign up to set email alerts
|

First Description of the Hyperpnea–Hypopnea Periodic Breathing in Patients with Interstitial Lung Disease-Obstructive Sleep Apnea: Treatment Implications in a Real-Life Setting

Abstract: There is evidence that hypopneas are more common than apneas in obstructive sleep apnea (OSA) related to idiopathic pulmonary fibrosis (IPF). We investigated the frequency distribution of hypopneas in 100 patients with interstitial lung diseases (ILDs) (mean age 69 yrs ± 7.8; 70% males), including 54 IPF cases, screened for OSA by home sleep testing. Fifty age- and sex-matched pure OSA patients were included as controls. In ILD-OSA patients the sleep breathing pattern was characterized by a high prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…It can be triggered by hypoxaemia and hypocapnia occurring during sleep, altitude exposure, stroke, heart failure 3 and interstitial lung disease. 4 This phenomenon has previously been described in hypobaric hypoxia during exercise 5 and sleep 6 and, experimentally, in normobaric hypoxia in healthy young adults and athletes. 7 8 Guidelines indicate supplemental oxygen if there is a fall in SpO 2 below 85% or the use of continuous positive airway pressure (CPAP) devices in patients with already diagnosed sleep disturbances requiring them.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…It can be triggered by hypoxaemia and hypocapnia occurring during sleep, altitude exposure, stroke, heart failure 3 and interstitial lung disease. 4 This phenomenon has previously been described in hypobaric hypoxia during exercise 5 and sleep 6 and, experimentally, in normobaric hypoxia in healthy young adults and athletes. 7 8 Guidelines indicate supplemental oxygen if there is a fall in SpO 2 below 85% or the use of continuous positive airway pressure (CPAP) devices in patients with already diagnosed sleep disturbances requiring them.…”
mentioning
confidence: 66%
“…In a recent report of patients with obstructive sleep apnoea related to IPF, oxygen rather than CPAP was more effective for treating periodic breathing. 4 The present report pictures periodic breathing during a diagnostic normobaric HAST at rest in an IPF patient. This finding could predict its manifestation during a commercial flight, where we found no data on its occurrence.…”
mentioning
confidence: 75%
“…Several studies have found that OSA is common in subjects with IPF and ILD [ 10 – 37 ]. Some findings of prospective studies, including ours, on the prevalence of OSA in IPF and ILD populations are presented in Table 4 [ 15 , 16 , 18 , 22 28 , 30 , 32 37 ]. This search was not systematic, but includes all the studies (with sample size > ten subjects) reported in a recent systematic review on the topic [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypopnoea is more common than apnoeas in patients with IPF/ILD, with the hypothesis that some are more vulnerable to sleep‐related ventilatory control instability (enhanced loop gain) due to chronic hypoxaemia 131 . Patients exhibiting the enhanced loop gain endotype (rather than predominantly upper airway collapse endotype) may respond to oxygen supplementation during sleep rather than CPAP, however, further research is needed 132 OSA and nocturnal hypoxaemia occur frequently in patients with IPF and other fibrotic lung diseases.…”
Section: Pharmacological Therapymentioning
confidence: 99%